Uganda : Third Review Under the Policy Support Instrument, Request for Waiver of Nonobservance of an Assessment Criterion, and Request for Modification of Assessment Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents key findings of the Third Review for Uganda under the policy support instrument. Monetary policy has been tightened significantly to reduce core inflation, supported by a contractionary fiscal stance. All but one of the seven quantitative assessment criteria were met at end-June; most structural benchmarks were met, although several with delay. Tighter monetary and fiscal policies in the near term aim to reduce inflation rapidly, while medium-term policies strive to create fiscal space to support stepped-up public infrastructure investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet